Application Of A Project-Based Learning Model To Improve Learning Outcomes And Critical Thinking Ability - Bayu, Bayu Yudho Baskoro; Langandriansya Dwi Yanto; M. Kurniawan (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the effectiveness of the implementation of the Project Based Learning (PjBL) model in improving learning outcomes and critical thinking skills of students in the Nautical Skills subject. The background of this study departs from the need for more contextual, applicable learning, and able to develop higher-order thinking skills in cadets at maritime schools. The methodology used is a qualitative approach with a classroom action research design through observation, interviews, documentation, and analysis of learning outcomes. The subjects of the study were cadets in the maritime study program who took the Nautical Skills subject. The results showed that the implementation of PjBL was able to increase learning activity, collaboration skills, and conceptual understanding of students. In addition, students' critical thinking skills experienced a significant increase, indicated by the ability to analyze maritime problems, formulate solutions, and make decisions based on field data. The improvement in learning outcomes is seen in the acquisition of higher average grades compared to before the implementation of PjBL, as well as more evenly distributed competency achievements. The conclusion of this study is that the Project Based Learning model is effectively applied to the Nautical Skills subject to improve learning outcomes and critical thinking skills. The research recommendations emphasize the need for sustainable implementation, adequate support for practical facilities, and strengthening the capacity of educators in designing and managing learning projects relevant to the maritime world.